Color Perception and Attentional Load in Dynamic, Time-Constrained Environments - Hüttermann, Stefanie; Smeeton, Nicholas J.; Ford, Paul R.; Williams, A. Mark (Frontiers in Psychology, 2019)
The capacity to perceive colour in the peripheral field has attracted research interest for more than a decade. There is evidence that sensitivity to red-green colour variations is lower than for yellow-blue in peripheral vision. Whether, and to what extent, colour vision affects the visual focus of attention, which is normally much smaller than the visual field, has not yet been examined. We used a sport-specific decision-making task to assess whether the colour of the jersey worn by players appearing in the periphery influences decision making by affecting the attentional and perceptual capabilities. Pairs of players wearing chromatic (blue, yellow, red, green) and achromatic (black, white) coloured jerseys were briefly presented across a range of visual angles on a 6 m concave immersive screen. Participants were required to decide to whom to pass and recall relevant information. Findings indicate that colour perception changes vary with increasing visual angle, but that the focus of attention is too small to be influenced by jersey colour sensitivity. Decision-making performance decreases with increasing visual angle, but is not influenced by colour. The implications for decision-making processes in sport and other professional domains are discussed.